Diverse Genome Topologies Characterize Dosage Compensation across Species. Issue 4 (April 2019) - Jordan, William; Rieder, Leila E.; Larschan, Erica
Abstract : Dosage compensation is the process by which transcript levels of the X chromosome are equalized with those of autosomes. Although diverse mechanisms of dosage compensation have evolved across species, these mechanisms all involve distinguishing the X chromosome from autosomes. Because one chromosome is singled out from other chromosomes for precise regulation, dosage compensation serves as an important model for understanding how specific cis -elements are identified within the highly compacted 3D genome to co-regulate thousands of genes. Recently, multiple genomic approaches have provided key insights into the mechanisms of dosage compensation, extending what we have learned from classical genetic studies. In the future, newer genomic approaches that require little starting material show great promise to provide an understanding of the heterogeneity of dosage compensation between cells and how it functions in nonmodel organisms. Highlights: Dosage compensation equalizes transcript levels on the X chromosome with those on autosomes. Dosage compensation serves as a model for understanding how specific cis -elements are collectively targeted for coordinated regulation within the genome. Genomic approaches to study chromatin and 3D genome organization have provided new insights into dosage compensation.